Applying TOE Framework for Researching the Intention of Adopting Social Media in 2-3-Star Hotels in Hanoi - Huong Giang Vu; Thanh Trung Nguyen; Thi Hoang Giang Ngo; Le My Vu (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: The study aims at unraveling the factors that impact the intention of adopting social media in 2–3-star hotels in Hanoi. Method: A mixed-methods research design was adopted, synergizing both qualitative and quantitative approaches to afford a comprehensive exploration of the research objectives. Result: Qualitative insights from in-depth interviews reveal participants' perspectives on technology, organizational, and environmental contexts. Quantitative findings from structured questionnaires affirm that user-friendly platforms, management support, industry competition, and guest expectations positively influence adoption intentions. These insights highlight the complex interplay between technological attributes, organizational dynamics, and environmental factors in shaping hotels' inclination to integrate social media platforms. Contribution: The study's theoretical contributions is achieved through the academic discourse. The synthesis of empirical revelations with established theories enriches the theoretical fabric, offering insights that resonate beyond this study's scope. The alignment with TOE framework extends the conceptual underpinnings of social media adoption within the hospitality domain. In practical terms, this study empowers hotel practitioners with actionable insights. The emphasis on management support, resource allocation, guest-centric engagement, and strategic adaptation furnishes practitioners with a compass to navigate the complex landscape of social media integration in 2-3-star hotels in Hanoi.